COVID‐Apps: Misdirecting Public Health Attention in a Pandemic. (5th August 2021) - Erikson, Susan
Abstract: When there is no vaccine for a disease, 'Test, Trace, Treat/Isolate' is the public health go‐to directive. During the COVID‐19 pandemic, mobile phone apps are designed to improve on this. But COVID‐apps have not been effective as a public health tool. Countries spend millions to develop them, yet they have been shown to have terrible return on investment. This commentary explores why COVID‐apps are generally championed and provides three brief case studies (Germany, Sierra Leone, Canada) of non‐app public health success. In conclusion, I argue that we need to get our public health care priorities straight: Better and more testing; increased investment in manual contact tracing and treatments; hospitalization when necessary; and wrap‐around care – assistance with groceries, cleaning, child‐ or eldercare responsibilities, telehealth doctor appointment hookups – for sick people in home isolation. Abstract : Invest in better and more testing; bankroll manual contact tracing; finance treatment and hospitalization, as well as wrap‐around care for the sick in‐home isolation, including assistance with groceries, cleaning, child‐ or eldercare responsibilities, and telehealth doctor appointment hookups.